Light‐intensity and moderate‐to‐vigorous intensity physical activity among older adult breast cancer survivors with obesity: A narrative review - Gordon, Brett R.; Caru, Maxime; Blair, Cindy K.; Bluethmann, Shirley M.; Conroy, David E.; Doerksen, Shawna E.; Hakun, Jonathon G.; Sturgeon, Kathleen M.; Potiaumpai, Melanie; Sciamanna, Christopher N.; Schmitz, Kathryn H. (Cancer medicine (Malden, MA), 2022)
Background With an aging population, rising incidence of breast cancer, improved survival rates, and obesity epidemic, there will be a growing population of older adult breast cancer survivors with obesity. This complex population, often with multimorbidity, is at risk for several poor health outcomes, including recurrence, cardiovascular disease, dementia, and diabetes, and a number of deleterious symptoms, including a worsened inflammatory profile, breast cancer‐ related lymphedema, mobility disability, cognitive impairment, anxiety, and depressive symptoms. A wealth of meta‐analytic and randomized controlled trial evidence show that adherence to World Health Organization and 2018 United States Physical Activity guidelines‐based levels of moderate‐to‐vigorous physical activity (MVPA) reduces risk of all‐cause mortality, and improves symptoms. However, few survivors engage in recommended levels of MVPA, and symptoms related to their multimorbidity may preclude engaging in sufficient levels of MVPA. Additional research of MVPA in this population is warranted; however, understudied light‐intensity physical activity (LIPA) may be a more pragmatic target than MVPA among this complex population facing extensive challenges meeting MVPA recommendations. Large benefits are likely to occur from increasing these survivors' total activity, and LIPA prescriptions may be a more pragmatic approach than MVPA to aid this transition. Methods We present a broad, narrative review of the evidence for MVPA and LIPA in this population on an array of health outcomes across the translational science spectrum (clinical, implementation, and public health), and identify a number of directions for future research focused on understanding the potential diverse health effects of LIPA. Conclusion Additional LIPA research is warranted, as LIPA prescriptions may be a pragmatic strategy to effectively promote physical activity to this complex population.